PEMAKNAAN REZIM PEMILU PASCA PUTUSAN MK NOMOR 55/PUUXVII/2019 - Savitri, Winny; Andiani, Anisa Dwi; Mukhammad, Aden Fadli (2024)
The legal basis for transferring regional head election dispute resolution is regulated in article 236C of Law no. 12 of 2008 concerning amendments to Law no. 32 of 2004 concerning Regional Government. This is based on the transfer of election status from the Regional Government regime to the Election Regime. The change in status from Pilkada to Election regime has implications for the transfer of authority in resolving disputes from the Supreme Court to the MK. As regulated in article 1 point 4 of Law no. 22 of 2007 concerning General Election Organizers which states that the Election of Regional Heads and Deputy Regional Heads is an election to elect regional heads and deputy regional heads directly in the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. From this statement there is an important question regarding the alleged norm dispute between Law no. 22 of 2007 concerning Election Organizers with the 1945 Constitution, because article 22E paragraph (2) of the 1945 Constitution states that General Elections are held to elect members of the People's Representative Council, Regional Representative Council, President and Vice President, and Regional People's Representative Council. So from these two articles it can be seen that there is an indication of inconsistency in the law makers regarding election terminology as regulated in the 1945 Constitution. In the Constitutional Court decision no. 55/PUU-XVII/2019, the Constitutional Court presented a number of other examples of new simultaneous elections which include regional elections in the simultaneous flow. In the Constitutional Court decision no. 55/PUUXVII/2019 was not included in the election regime because it can be seen from the Constitutional Court Decision No. 48/PUU-XVII/2019 and Constitutional Court Decision No. 55/PUU-XVII/2019 where the Constitutional Court did not respond to the theory of regime segregation initiated by the Constitutional Court in Constitutional Court Decision No. 97/PUU-XI/2013. In Constitutional Court Decision No. 55/PUU-XVII/2019 does not want to be trapped in using the regime separation line of thinking again and instead provides a new idea, namely the simultaneity of elections, namely National Elections and Local Elections (which include Regional Elections).